2002
DOI: 10.1111/j.1748-121x.2002.tb00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Representations of the (woman) judge: Hercules, the little mermaid, and the vain and naked Emperor

Abstract: This paper reconsiders images of the judge and, in particular, the position of the woman judge using fairy tale and myth. It begins by exploring the actuality of women's exclusion within the judiciary, traditional explanations for this and the impact of recent changes. It goes on to consider the image of the Herculean judge, arguing that whilst we may view him as an ideological construct, or even as a fairy tale, we routinely deny this to ourselves and to others. This both ensures the normative survival of Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 4 publications
0
13
0
4
Order By: Relevance
“…Apart from the essentialist assumption that judges can or should represent their gendered, raced or religious constituencies in such a mechanistic fashion (Albertyn 2014, 263-4, 267-9), this implies an expectation that all women are aware of and committed to the feminist project while men are per definition opposed to substantive gender equality. Whereas the mere presence of female judges can been said to disrupt implicitly masculine symbols of legal authority and reasoning, (Cowan 2006, 317;Rackley 2002), experience in the South African Constitutional Court has shown that male judges can be similarly committed and very effective in disseminating feminist views (Bonthuys 2008b, 30-33).…”
Section: Conclusion: Women Feminism and Transformationmentioning
confidence: 97%
“…Apart from the essentialist assumption that judges can or should represent their gendered, raced or religious constituencies in such a mechanistic fashion (Albertyn 2014, 263-4, 267-9), this implies an expectation that all women are aware of and committed to the feminist project while men are per definition opposed to substantive gender equality. Whereas the mere presence of female judges can been said to disrupt implicitly masculine symbols of legal authority and reasoning, (Cowan 2006, 317;Rackley 2002), experience in the South African Constitutional Court has shown that male judges can be similarly committed and very effective in disseminating feminist views (Bonthuys 2008b, 30-33).…”
Section: Conclusion: Women Feminism and Transformationmentioning
confidence: 97%
“…Increasing judicial diversity “is necessary in order to maintain public confidence and trust, that is, to ensure the legitimacy of the judiciary as a whole” (Rackley 2002, 609; see also Kenney 2008b; Handsley 2006; Thomas 2005). Women on the bench reflect the society being judged and so maintain public confidence (Genn 2008; Malleson 2006b, 2003a; Thomas 2005; Rackley 2002). Courts as gendered institutions jeopardise their own claims of neutrality and impartiality (Thomas 2005; Malleson 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…Emphasising the need for women in the judiciary can imply that only women have a gender, which then raises concerns about bias (Minow 1992), in contrast to the presumably interchangeable benchmark white men “who are vested with impartiality, neutrality and objectivity” (Kenney 2010, 439). The recognition that gender matters, in judicial selection and in judging, exposes the contested nature of the judicial role and the core concepts of impartiality and neutrality (Maveety 2010; Genn 2008; Malleson 2006a; Thomas 2005; Rackley 2002).…”
Section: Introductionmentioning
confidence: 99%
“…She argues that, like the Little Mermaid in Hans Christian Anderson's fairy tale, for female judges to join this society they have to lose their voice. 70 The imperial history of law can offer a genealogy of this myth, uncovering not only how the judge has become figured as male but also as white. It might also explore how the myth has been appropriated, transfigured, challenged and subverted in postcolonial contexts as non-white and female bodies have attempted to occupy the imprints left by this somatic norm associated with the imperial judge.…”
Section: The Imperial Genealogy Of a Mythmentioning
confidence: 99%